A 9T FinFET SRAM cell for ultra-low power application in the subthreshold regime - Shilpi Birla; Neha Singh; Neeraj K. Shukla; Sidharth Sharma (Bulletin of Electrical Engineering and Informatics, 2021)
Due to the scaling of the CMOS, the limitations of these devices raised the need for alternative nano-devices. Various devices are proposed like FinFET, TFET, CNTFET. Among these, the FinFET emerges as one of the promising devices which can replace the CMOS due to its low leakage in the nanometer regime. The electronics devices are nowadays more compact and efficient in terms of battery consumption. The CMOS SRAMs have been replaced by the FinFET SRAMs due to the scaling limitations of the CMOS. Two FinFET SRAM cells have been which power efficient are and having high stability. Performance comparison of these cells has been done to analyze the leakage power and the static noise margins. The simulation of the cells is done at 20 nm FinFET technology. It has been analyzed that the write margin of improved 9T SRAM cell achieves an improvement of 1.49x. The read margin is also showing a drastic improvement over the existing cells which has been compared in the paper. The hold margin was found to be better in the case of the proposed SRAM cell at 0.4 V. The gate length has been varied to find the effect on read margin with gate length.